The maintenance management and challenges of 4-star hotel in Ipoh, Perak / Muhammad Iman Abdul Hamid - Abdul Hamid, Muhammad Iman (Universiti Teknologi MARA (UiTM), 2024)
This research investigates the maintenance management practices of 4-star hotels in Ipoh, Perak, with a focus on understanding the challenges faced by hotel managers. The study aims to identify 4-star hotel rated in Ipoh, Perak with the current maintenance management practices employed in these establishments and to find the challenges that faced by hotel managers. Utilizing a qualitative research methodology, data through open-ended interviews with hotel managers, supplemented by secondary data from relevant literature is created. The findings reveal key themes related to maintenance management practices, including the importance of proactive maintenance, staff training, and the integration of technology in operations. Additionally, the research highlights the challenges faced by hotel managers, such as budget constraints and the need for continuous staff development.